Research on mechanical and gas seepage characteristics of coal-containing gas in the process of unloading confining pressure before and after peak strength. (November 2015) - Deng, T.; Li, T.; Qiao, D.; Li, K.
Abstract : This research studied the effects of a triaxial stress thermal–hydromechanical coal-containing-gas permeameter on mechanical and gas seepage characteristics under different confining pressures, different initial axial stress and different unloading speeds of the confining pressure. The results showed that in the process of unloading the confining pressure before peak strength, the strain (permeability) could be divided into three stages. As the unloading speed was increased the duration of the initial axial stress time would decrease, along with the duration of the axial stress platform. The permeability was closely related to the unloading of the confining pressure and the initial axial stress, which, when increased, would lead to accelerated strain growth. Additionally, the results of the experiment that unloaded the confining pressure after peak strength showed that strain (permeability) could be divided into two stages, and when compared to the experiment done before peak strength, the duration of the axial stress platform was greatly shortened.